Lalka i nieobecność. Kilka uwag o bohaterach Wampira Władysława Stanisława Reymonta - Kucab, Mateusz (Dydaktyka Polonistyczna, 2019)
The article attempts to determine in synthetic way the most relevant spaces of choice as well as activities of the characters of The Vampire by Władysław Stanisław Reymont. Disputing with other researchers, we try to portray the characters as thespians who are subordinate to the mechanism of theatre (theatricality) as well as enmeshed with relations of dominance and exploitation (vampiric situation). Having compared the novel with selected dramas by Henrik Ibsen, we demonstrate parallels in subjects and issues that were drawn out by the dramaturgy of the epoch: illusoriness of life, lies of convention, prevalence in family as well as manipulation.